Introduction: Descent from Israel and Jewish Identities in the Pacific, Past and Present. Issue 3 (8th October 2015) - Newland, Lynda; Brown, Terry M.
Abstract: This Introduction to this Special Issue of Oceania, 'Descent from Israel: Jewish Identities in the Pacific, Past and Present', sets the historical context of European interest in Pacific peoples as descended from the 'Lost Tribes' of the biblical Hebrews. After surveying the way in which Pacific Christians in the past and present have adopted a Jewish identity, whether through genealogy, biblical and theological interpretation, and/or deep interest in the State of Israel, we then contextualise and summarise the scholarship that follows: on Jewish identity as adopted by churches and religious movements in Fiji, Solomon Islands and Papua Guinea, as well as a final reflection on their significance for Judaism today.